Role Facebook Use and Addiction on Academic Achievement: A Pilot Study on Undergraduate Students - N. Sharmin; O. Ahmed; Z. Sharmin (University of Sofia, 2019)
For the past few years Facebook becomes one of the most popular social net-working website around the world. It is widely used website among the stu-dents for fulfilling their needs of interaction. Excessive usage of Facebook that leads to addiction on Facebook gets huge concern among scientific community. There were very studies that assess the impact of the Facebook usage and addiction on academic achievement. The present study was aimed to assess the impact of these factors on the academic results of undergrad students. A booklet, included questions regarding academic achievement, Facebook usage, and the Bergen Facebook Addiction Scale, was administered on a non-representative sample of 161 undergrad students. Results suggested the Facebook use and addiction as significant negative predictors of academic achievement. This study also explored significant mean differences in Facebook addiction score and academic achievement by gender. From the present study findings, it is time to rethink about controlling the students' usage of social media like Facebook.